Biodegradation and decolorization of methylene blue, reactive Black-5, and toluidine blue-O from an aqueous solution using the polyphenol oxidase enzyme - Uddin, Jalal; Idrees, Muhammad; Ahmed, Humam; Batool, Saima; Rahman, Tanzeel Ur; Mehmood, Shahzil; Tanoli, Asad Khan; Muhsinah, Abdullatif Bin; Ullah, Hidayat; Musharraf, Syed Ghulam (Frontiers in Sustainable Food Systems, 2024)
In this study, a copper-containing polyphenol oxidase (PPO) enzyme was extracted from the selected agricultural food products, i.e., Mangifera indica (L.), Solanum tuberosum (L.), and Luffa cylindrica (L.), which has efficiently degraded the azo dyes (Methylene blue, Reactive Black-5, and Toluidine Blue-O) into less toxic compounds. After preparing the dye solution at various concentrations, the PPO enzymes extracted with phosphate buffer were incubated with it for 2 hours. The percentage of decolorization was estimated by using the unprocessed dye solution. The degraded products were characterized by UV–vis and FT-IR. All sets of experiments followed pseudo-first-order kinetics. The highest kinetic degradation rate constant was observed at kt = 0.0213 min─1 (R2 = 0.9258) and kt = 0.0244 min─1 (R2 = 0.7627) in reactive black-5 from Mangifera indica (L.) and Solanum tuberosum (L.), respectively. The enzyme extracted from the peel of Solanum tuberosum (L.) decolorized Reactive Black-5 and Toluidine Blue-O dyes to a greater extent, i.e., 83.29 and 70.84% with reaction times of 120 and 90 min, respectively.